Effect Of Diabetes Mellitus Heart Disease And Vaccine On Mortality Rate In COVID 19 Patients In Iraq (The Review of Diabetic Studies, 2025)
Background, COVID-19 has created a significant global health concern, diabetes and heart disease are most commonly seen in severely ill cases. A retrospective analytical study was carried among 105 patients, who were COVID-19 cases confirmed by PCR.Objective, to estimate the effect of diabetes mellitus, heart disease, and vaccine on the mortality rate in COVID-19 patients in IraqMethodology, Clinical data, vaccination background, and comorbidity status (heart disease and diabetes mellitus) were recorded. Biochemical parameters such as random blood sugar (RBS), glycated hemoglobin (HbA1c), and body mass index (BMI) were measured. Death was declared as the primary outcome. Statistical analysis was done using Jamovi, applying chi-square tests, t-tests, as well as logistic regression to determine independent predictors of death.Results, out of 105 COVID-19 patients, 19 (18.1%) died. Heart disease was significantly associated with mortality (χ²=14.1, p